Cloud Computing and Its Features: An Advanced Approach - Mitra, Manu (Recent Advances in Mathematical Research and Computer Science Vol. 3, 2021)
Cloud Computing is a technology that utilizes internet for storing and managing data on remote servers. They can be classified as Public cloud – it’s owned and operated by a third party cloud service providers, Private cloud – It refers to computing resources used exclusively by a single business or organization, and Hybrid cloud – It combines public and private clouds, bound together that allows data and applications to be shared between them. Few applications are discussed for Cloud Computing.